Particularities of concluding, amending and terminating labour contracts under atypical forms of hired workers’ employment - Husarov, O.; Гусаров, О. (Підприємництво, господарство і право. - 2022. - № 12. - С. 12-17, 2022)
Розкрито сутність, зміст та особливості укладення, зміни та припинення трудових договорів у разі нетипових форм зайнятості найманих працівників. Акцентовано увагу на тому, що не досить врегульованим є питання зміни умов трудового договору у разі нетипових форм зайнятості, адже нині воно регулюється аналогічно до загальних категорій працівників, що, безумовно, не відповідає дійсності та потребам відповідних форм зайнятості. З’ясовано, що зміна умов трудового договору у разі нетипових форм зайнятості найманих працівників – це складний за своєю сутністю та змістом процес, його особливості зумовлюються: специфікою трудових правовідносин, які виникають між працівниками, що працюють дистанційно, надомно чи за гнучким графіком; особливостями організації процесу праці, робочого місця тощо.

The purpose of the article is to reveal the particularities of concluding, amending and terminating employment contracts in the context of atypical forms of hired workers’ employment. Results. Relying on the analysis of scientific views of scholars and provisions of legislation in force, the article reveals the essence, content and particularities of concluding, amending and terminating employment contracts in case of atypical forms of hired workers’ employment. The author emphasises that the issue of changing the terms of an employment contract in atypical forms of employment is insufficiently regulated, since it is currently regulated similarly to general categories of employees, which certainly does not correspond to the reality and needs of the relevant forms of employment. It is established that changing the terms and conditions of an employment contract in the context of atypical forms of hired workers’ employment is a complex process in nature and content, and its particularities are determined by: the specifics of labour relations arising between employees working remotely, at home or on a flexible schedule; particularities of organisation of the labour process, workplace, etc. Conclusions. It is concluded that nowadays the procedure for concluding, amending and terminating employment contracts in case of atypical forms of hired workers’ employment is somewhat vague and does not allow for the specifics of the employment activities of the category of employees under study. In particular, the issue of changing the terms of an employment contract is insufficiently regulated, since it is currently regulated similarly to general categories of employees, which certainly does not correspond to the reality. Therefore, among the particularities of concluding, amending and terminating employment contracts in atypical forms of hired workers’ employment, the following should be highlighted: ambiguity of regulatory mechanism, because, on the one hand, the legislator has regulated the issue of concluding an employment contract in a fairly comprehensive manner, but the amendment and termination of the latter are enshrined in the legislation in force in a rather superficial manner; the terms of an employment contract are changed allowing for the specifics of the organisation of the workplace of the category of employees under study, working hours and rest periods; an employment contract is terminated on the general principles provided for by the Labour Code of Ukraine.

Раскрыты сущность, содержание и особенности заключения, изменения и прекращения трудовых договоров в случае нетипичных форм занятости наемных работников. Акцентировано внимание на том, что недостаточно урегулирован вопрос изменения условий трудового договора в случае нетипичных форм занятости, ведь сейчас он регулируется аналогично общим категориям работников, что, безусловно, не соответствует действительности и потребностям соответствующих форм занятости. Выяснено, что изменение условий трудового договора в случае нетипичных форм занятости наемных работников – это сложный по своей сути и содержанию процесс, его особенности обусловливаются: спецификой возникающих трудовых правоотношений между работниками, работающими дистанционно, надомно или по гибкому графику; особенностями организации процесса труда, рабочего места и т.д.
Особливості укладення, зміни та припинення трудових договорів у разі нетипових форм зайнятості найманих працівників
Keywords: трудові правовідносини; labor relations; трудовые правоотношения; трудовий договір; employment contract; трудовой договор; припинення трудового договору; termination of the employment contract; прекращение трудового договора; нетипові форми зайнятості; atypical forms of employment; нетипичные формы занятости; наймані працівники; hired workers; наемные работники; зміна умов трудового договору; changing the terms of the employment contract; изменение условий трудового договора